Relative Time Delay and Absolute Time Delay (Global Journal of Science Frontier Research, 2016)
This paper has explained that, the motion can be divided into two types, i.e. relative motion between two objects and circular motion unrelated to relative motion (also known as absolute motion). Time delay resulted from relative motion is referred to as relative time delay; time delay caused by circular motion is referred to as absolute time delay. Relative time delay refers to a time delay effect obtained by an observer when observing another reference system being in motion; absolute time delay refers to a real time delay of object being in motion. It is deduced that, the only way for human beings to achieve a real time delay situation is that: An observer can travel around the planet by spacecraft. The analyzed results show that, it is impossible for black hole to exist as a real matter. As a result, the time delay obtained after traveling around fixed star A1 by spacecraft shall be considered as the maximum absolute time delay obtained by human beings.
Keywords: special relativity; time interval; relative velocity; relative time delay; circular motion; absolute time delay; equivalence principle; black hole; ti